Návrh konceptu onboardingu a adaptace zaměstnanců ve vybrané společnosti. - Couralová, Monika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Diplomová práce se zabývá procesem onboardingu a adaptace zaměstnanců ve společnosti Renocar, a.s. Teoretická část představuje koncepci řízení lidských zdrojů se zaměřením na získávání a adaptaci zaměstnanců. Analytická část se zabývá současným stavem procesů ve společnosti a výzkumem vnímání samotného procesu zaměstnanci. Na základě výsledků z provedených analýz byly vypracovány jednotlivé návrhy změn v procesu onboardingu a následné adaptace zaměstnanců.

The thesis deals with the process of onboarding and adaptation of employees in Renocar, a.s. The theoretical part presents the concept of human resource management with a focus on recruitment and adaptation of employees. The analytical part deals with the current state of the processes in the company and the research of the employees' perception of the process itself. Based on the results of the analyses, individual proposals for changes in the process of onboarding and subsequent adaptation of employees were developed.
Design of Onboarding Concept and Employee Adaptation in a Selected Company.
Keywords: zaměstnanec; zaměstnavatel; nábor; onboarding; adaptace; fluktuace; employee; employer; recruitment; onboarding; adaptation; fluctuation